The Effect of Using ICT Based on Learning Media to Studentsâ Learning Motivation - Suarman, Suarman; Mahdum, Mahdum; Suryati, Suryati (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study aims to determine the effect of using ICT based on learning media to studentâs learning motivation. The hypothesis of this study is: ICT based learning media is the determination of studentsâ learning motivation which has a positive influence. This survey method with technique using purposive sampling is applied. The type of data was primary data obtained by questionnaire. The technique of data analysis is regression analysis and independent sample T-test analysis with SPSS program. The result showed that using ICT based on learning media has a positive and significant effect on studentâs learning motivation.